The Impact of Artificial Intelligence on Supply Chain Resilience: An Empirical Study - Xu, Zhiwei (Transactions on Computer Science and Intelligent Systems Research, 2025)
The rapid development and widespread application of artificial intelligence (AI) across various industries have garnered significant attention. This paper investigates the impact of AI on supply chain resilience using data from A - share listed companies in China from 2012 to 2022. The findings indicate that AI has a significant positive impact on supply chain resilience, which remains robust after multiple robustness tests and endogeneity treatments. Heterogeneous analysis shows that the enhancing effect of AI on supply chain resilience is more pronounced in state - owned enterprises, enterprises audited by the Big Four, and enterprises in the eastern region. Mechanism analysis reveals that AI enhances supply chain resilience by promoting R&D innovation, optimizing resource allocation efficiency, and improving financing speed. These results suggest that AI application can effectively enhance the risk - resistance and recovery capabilities of supply chains, with significant implications for promoting enterprise digital transformation and improving supply chain management levels.